A Comparative Study of Authentic and Artificial Text-Based Reading Learning in Improving English Reading Comprehension - Yanti Anggraini (EDUJ : English Education Journal, 2024)
This study aimed to compare the effectiveness of authentic texts versus fabricated texts in improving reading comprehension among high school students learning English as a Foreign Language (EFL). Using a quasi-experimental design, the study involved two groups of students: an experimental group that was taught using authentic materials (e.g., news articles, short stories) and a control group that used fabricated texts specifically designed for educational purposes. Data were collected through pre-tests and post-tests on reading comprehension, a motivation questionnaire, and classroom observations. The results showed a significant improvement in reading comprehension scores and learning motivation in the experimental group compared to the control group. Authentic texts were found to be more engaging and relevant, boosting students' intrinsic motivation and active participation. The study concludes that integrating authentic materials into the EFL classroom can enhance reading skills and increase student engagement. Both authentic and fabricated texts play important roles in language learning, and their balanced use can provide a comprehensive approach to teaching reading comprehension.